The Properties of Concrete Containing Palm Oil Fuel Ash and Expanded Polystyrene Beads - Osman, Mohamad Hairi; Adnan, Suraya Hani; Wan Jusoh, Wan Amizah; Mazlin, Nurul Izlin (International Journal of Integrated Engineering, 2020)
This paper investigates the stress strain behaviour of concrete containing Palm Oil Fuel Ash and Expanded Polystyrene, axial compressive strength, tensile strength and modulus of elasticity. EPS-POFA concrete was prepared by substituting fine aggregates with EPS beads and cement replaced with POFA by 10%, 20% and 30%. Results of this study showed that EPS-POFA concrete exhibited low axial compressive strength, peak strain, tensile strength and elastic modulus when the EPS and POFA contents in concrete increased. However, the decrease in axial compressive strength of concretes with containing 10 to 20% EPS and POFA are suitable amount and acceptable to be applied on building structure as per stated in America Concrete Institute 318 with minimum specified compressive strength for structural concrete is 2500 psi (17 MPa). While, the failure of EPS-POFA concrete under axial compression gradually occurred and the concretes were able to retain the load after failure without full collapse. The slope of stress-strain curve of concretes with containing EPS and POFA was lower than that of normal concrete, demonstrating that the normal concrete more brittleness that EPS-POFA concretes.